Productive performance and cost effectiveness of broiler using three different probiotics in the diet (Bangladesh Journal of Animal Science, 2020)
The experiment reported here was an attempt to evaluate the effect of feeding three different probiotics to broilers on productive performance, meat yield and profitability of rearing for 42 days in an open sided house, at Bangladesh Agricultural University Poultry Farm. Two hundred fifty-six one-day old Indian River straight run broiler chicks were randomly allotted to four dietary treatments each of four replicates of 16 chicks each providing floor space of 1115 cm2 per bird. The basal diet was corn-soya and it was supplemented with different probiotics to make test diets. The dietary treatments were: basal diet (T1); basal diet supplemented with probiotic-1 (PB-1) at 1.0 g/kg feed (T2); basal diet supplemented with probiotic-2 (PB-2) at 1.0 g/kg feed (T3); basal diet supplemented with probiotic-3 (PB-3) at 0.5 g/kg feed (T4). Birds were fed starter diet from 0-21 days of age and grower diet from 22-42 days of age. Records were kept of performance traits and carcass yields by maintaining birds under identical management. Profitability was determined on termination of the trial. Performance and carcass yield data were statistically analyzed employing SAS Computer Package Program (SAS, 2009). Results showed no variation (P>0.05) in growth performance and meat yield characteristics of commercial broilers irrespective of types of probiotic supplementation. However, feed intake increased (P